2014
DOI: 10.1021/jf5048089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Evaluation of Triketone-Containing Quinazoline-2,4-diones

Abstract: Exploring novel 4-hydroxyphenylpyruvate dioxygenase (EC 1.13.11.27, HPPD) inhibitors is one of the most promising research directions in herbicide discovery. To discover new triketone herbicides with broad-spectrum weed control as well as excellent crop selectivity, a series of (total 52) novel triketone-containing quinazoline-2,4-dione derivatives were synthesized and further bioevaluated. The greenhouse testing indicated that many of the newly synthesized compounds showed better or excellent herbicidal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 25 publications
0
94
1
Order By: Relevance
“…(The crystal structures have been deposited at the Cambridge Crystallographic Data Centre and allocated the deposition numbers CCDC 1450978 and CCDC 1450980.) To synthesize the enol ester ( J ), the acid ( I ) is generally transformed into the corresponding acid chloride using SOCl 2 or ClCOCOCl . The limitation of this method is that it can only be utilized to prepare acid chlorides that are stable and not sensitive to SOCl 2 , ClCOCOCl or heat.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(The crystal structures have been deposited at the Cambridge Crystallographic Data Centre and allocated the deposition numbers CCDC 1450978 and CCDC 1450980.) To synthesize the enol ester ( J ), the acid ( I ) is generally transformed into the corresponding acid chloride using SOCl 2 or ClCOCOCl . The limitation of this method is that it can only be utilized to prepare acid chlorides that are stable and not sensitive to SOCl 2 , ClCOCOCl or heat.…”
Section: Resultsmentioning
confidence: 99%
“…All related work was conducted using the methods reported previously. 8,16,17,[23][24][25][26] The IC 50 values are summarized in Table 1.…”
Section: Hppd Inhibition Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, triketone HPPD herbicides with triketone and aromatic moieties are the most widely studied . For example, many studies have reported that the modification of the aromatic part of triketone derivatives is an effective way to obtain new inhibitors with improved potency. All the modified triketone derivatives mainly focused on aromatic component, which is replaced by heterocycles, aliphatic side chains, fused heterocycles and fused aromatics …”
Section: Introductionmentioning
confidence: 99%